PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP MOTIVASI DAN KEMAMPUAN BERPIKIR KRITIS SISWA DALAM MATA PELAJARAN IPAS KELAS V - Rusita Agustina, Maya; Wahyu Sukartiningsih; Benny Agus Pribadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Student-centered learning has an influence on improving critical thinking skills and learning motivation of students. Science learning, with the complexity and dynamics of the material taught, provides a good opportunity for the development of critical thinking skills. This study aims to determine the effect of the problem-based learning model on the motivation and critical thinking skills of students in the subject of science for grade V. This study is a quantitative study with a quasi-experimental design with a nonequivalent control group design model. The subjects in this study were 46 students of grade V. The instrument in this study used a questionnaire for the motivation variable and a test for students' critical thinking skills. The data analysis method through data analysis prerequisites with data distribution normality tests and data homogeneity tests, then hypothesis testing using the t-test (independent sample t-test). The results of this study indicate that the problem-based learning model has a significant effect on the learning motivation of grade V students in the subject of science at MI Terpadu Bina Putra Cendikia Ponorogo. The problem-based learning model has a significant effect on the critical thinking skills of grade V students in the subject of science at MI Terpadu Bina Putra Cendikia Ponorogo. This is proven by hypothesis testing that there is a significant difference between the critical thinking abilities of students in the experimental class and the control class.